2018
DOI: 10.1002/qua.25728
|View full text |Cite
|
Sign up to set email alerts
|

Mg3F7: A superhalogen with potential for new nanomaterials design

Abstract: The stability of the Mg3F7 cluster and its ability to ionize nanoparticles has been investigated theoretically. At the CCSD(T) level of theory, the Mg3F7 cluster has been confirmed to be superhalogen due to its high adiabatic electron affinity (7.9 eV). The corresponding daughter anionic species (Mg3F7−) displays a highly symmetric (C3v) umbrella‐like structure and magic cluster stability. The extra electron of the Mg3F7− anion aggregates on the terminal fluorine ligands with non‐negligible distribution occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(70 citation statements)
references
References 74 publications
3
66
1
Order By: Relevance
“…For instance, the superhalogen properties of titanium-related species are very limited . Since a plenty of studies have demonstrated that polynuclear clusters can form superhalogens more effectively, ,,, it is very interesting to see whether the polynuclear clusters of titanium can behave as a new class of superhalogens.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the superhalogen properties of titanium-related species are very limited . Since a plenty of studies have demonstrated that polynuclear clusters can form superhalogens more effectively, ,,, it is very interesting to see whether the polynuclear clusters of titanium can behave as a new class of superhalogens.…”
Section: Introductionmentioning
confidence: 99%
“…These stable clusters are often referred to as magic clusters and includes (i) clusters of simple metals (e.g., Na 8 , Na 20 , Na 40 , Na 58 , Na 92 ) and (ii) clusters of noble gas atoms (e.g., Xe 13 , Xe 55 , Xe 147 ) . Very recently, I have investigated a magic cluster with molecular composition (Mg 3 F 7 ) − . On the basis of an ab initio calculations, I confirmed that this magic cluster owes its unusual stability to the superhalogen character of its corresponding neutral parent (Mg 3 F 7 ).…”
Section: Introductionmentioning
confidence: 87%
“…On the basis of an ab initio calculations, I confirmed that this magic cluster owes its unusual stability to the superhalogen character of its corresponding neutral parent (Mg 3 F 7 ). The Mg 3 F 7 – superhalogen anion, owing to its enlarged stability, have the potential to serve as building blocks of a new class of salts with superoxidizing properties. …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Besides, theoretical calculations have been successfully applied to predict EAs for many species. 611 A number of theoretical methods such as ab initio methods and density functional theory have been widely used in such kinds of studies. 1214 In particular, EA can be used as an important indicator to identify superhalogens, which are defined as species with higher EAs than that of chlorine atom.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the electron affinity (EA) is a significant property related to chemical stabilities and reactivities of corresponding molecules. For example, superhalogens with high electron affinities exhibit superior chemical reactivity and strong oxidation properties. Several methods have been used to measure EAs experimentally, and the most effective one is based on the photoelectron detachment. , Besides, theoretical calculations have been successfully applied to predict EAs for many species. A number of theoretical methods such as ab initio methods and density functional theory have been widely used in such kinds of studies. In particular, EA can be used as an important indicator to identify superhalogens, which are defined as species with higher EAs than that of chlorine atom. Since Boldyrev and Gutsev first proposed the superhalogen examples of MX k +1 in the early 1980s, there are many kinds of superhalogens that were identified by now, such as MX 3 (M = Be and Mg, Ca; X = Cl and Br), Mg 2 X 5 (X = F and Cl), and so on. , The EA value can be as high as 9.7 eV for Gd­(BF 4 ) 4 . Besides, superhalogen properties can be manifested by the vertical detachment energies (VDEs) of the corresponding anions.…”
Section: Introductionmentioning
confidence: 99%